Food Addiction and Substance Addiction in Women: Common Clinical Characteristics - Hardy, Raven (Appetite, 2017)
Food addiction is characterized by poorly controlled intake of highly-palatable, calorically-dense, foods. While previous studies indicate that risk factors for food addiction are similar to substance use disorders (SUD), these studies have looked at food addiction and SUD in independent samples, limiting the ability to directly compare food addiction to SUD. The present study was conducted to assess rates of posttraumatic stress disorder (PTSD), depression, childhood and adult trauma exposure, as well as presence and severity of emotion dysregulation, in a sample of women (N=229) who either meet criteria for no addiction, food addiction only or SUD only. The prevalence of food addiction was 18.3% and the prevalence of SUD was 30.6% in this sample. Women with food addiction and women with SUD endorsed more depression and PTSD symptoms when compared with individuals with no addiction. Individuals with food addiction and SUD had higher total emotion dysregulation scores, specifically with difficulties in goal directed behaviors, non-acceptance of emotional responses, impulse control, limited access to emotion regulation strategies, and lack of emotional clarity, when compared to individuals with no addiction (all p’s<0.05). There were no differences in PTSD and depression symptoms and emotion dysregulation scores between food addiction and SUD groups (all p>0.05). However, women with SUD endorsed higher levels of total childhood (p<0.01) and adulthood trauma (p<0.01) as compared with women with no addiction or food addiction. These results suggest that women with food addiction and those with SUD share similar psychological characteristics and risk factors, with the exception of trauma histories. These findings have implications for the detection of risk for and treatment of these disorders.